An insight into physical activity level among pregnant women in Terengganu: a pilot study - Ain Widad, A.; Wee, B.S.; Rosliza, Y.; Marhazlina, M.; Mohd Razif, S.; Lin, L.P (2020)
Regular physical activity during pregnancy gives various health benefits for mothers. However, due to lack of exposure regarding the benefits of physical activity, a taboo among expecting mothers exist. The aims of this study are to determine the reliability of the Malay version of Pregnancy Physical Activity Questionnaires (PPAQ) and physical activity level of pregnant women in Terengganu. This cross-sectional study used self-administered questionnaires consist of sociodemographic characteristics and Malay version of PPAQ (PPAQ-Malay). The English version of PPAQ was translated to Malay by two linguistic expert and back translated to English for consistency. The data were analysed by using IBM SPSS version 23. A total of 23 pregnant women were recruited from two health clinics in Terengganu, aged between 22 to 41 years old. For the reliability test, PPAQ-Malay yielded a Cronbach’s Alpha of 0.733, and the Intraclass Correlation Coefficient (ICC) value range from 0.537 to 0.869, indicating an acceptable internal consistency. Most of the participants were in their third trimester (60.9%, n=14), while 30.3% were in second trimester (n=7). Majority of the pregnant women participated in light-intensity activities (mean 14.1 ± 10.8 MET-hr/week, 1.5-3.0 METs) in the form of household care giving (75.6 ± 63.9 MET-hr/week) and occupational type (70.2 ± 112.6 MET-hr/week). In conclusion, PPAQ-Malay can be accepted as a reliable tool to evaluate physical activity of pregnant women in Terengganu. Sufficient level of physical activity is needed to prevent pregnancy-related-complication. The taboo of being physically active during pregnancy should be corrected by revealing the benefits of physical activity.